Tren dan Perkembangan Business Intelligence di Era Digital - Waznah, Faiza Zayani; Rahmayani, Elysa; Harahap, Fatimah Zahra Matahaini; N, Nurbaiti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Business intelligence (BI) is the most important component involved in digital era. In fact, most MSMEs in Indonesia face different challenges in adopting BI technology compared to multinational companies that have mature resources. This study uses a qualitative method based on a systematic literature review to analyze how MSMEs that have successfully implemented BI show improvements in product innovation through market trend analysis, business continuity through predictive analytics, and customer satisfaction through service personalization. The Business Intelligence Research Framework is abundant, and the technological infrastructure that Indonesian SMEs follow follows a unique pattern with barriers such as capital constraints, technology limitations, and resistance to change. The research findings reveal that BI is crucial for supporting innovation, competitiveness, and operational efficiency in SMEs; however, its implementation requires this study to be offered as recommendations to companies seeking to leverage business intelligence, emphasizing the need for developing a BI implementation framework tailored to the local context. Theoretical and pragmatic implications for Indonesian SMEs, guidelines for government support in SME digitalization, and best practices for technology vendors in developing affordable and user-friendly BI solutions. This research makes a significant contribution to understanding the complexity of BI implementation in Indonesian SMEs and paves the way for further research focused on practical solutions to address existing contextual gaps.